Aplicación de tecnologías de medición 3D para la documentación arquitectónica y evaluación estructural caso Iglesia de Balbanera, Colta-Chimborazo - Espinosa Figueroa, Edison Fabricio (2021)
The tangible and intangible cultural heritage is the most representative way to publicize the identity of a city, which is why its importance in architecture since it represents its history and culture. Currently, tangible heritage is the one that has been most exposed and is at risk ofdeterioration, destruction orlos, dueto multiple causes or conditions ofnatural origin or human intervention. That is why, due to this problem, there is a need to have current technological tools for the due maintenance of tangible heritage, that allow each architectural element to be digitally recorded and documented to have reliable information on said object. The apps and informatics tools allow an optimization y the process of measuring and gathering information obtaining essential results in a specific study such as architectural documentation, enabling users to carry out tests, simulations, quantifications and evaluations of the objects analyzed. The purpose of this research work is to carry out the survey and structural evaluation of the Balbanera Church, an important heritage asset for the country using technological equipment such as the 3D scanner for the precise survey of the Church, applying a methodology based on a BIM information model (Building Information Model) for its architectural documentation and structural evaluation resulting in a manual for the use of 3D measurement technologies for subsequent interventions in heritage buildings not only at a professional level but also helps to update academic knowledge and contributes to research, analysis and interpretation of data from heritage buildings.